From risky places to safe spaces: Re-assembling spaces and places in Vancouver's Downtown Eastside. (September 2019) - Ivsins, Andrew; Vancouver Area Network of Drug Users,; Benoit, Cecilia; Kobayashi, Karen; Boyd, Susan
Abstract: Vancouver's Downtown Eastside (DTES) neighbourhood is commonly associated with stigmatized and criminalized activities and attendant risks and harms. Many spaces/places in this urban neighbourhood are customarily portrayed and experienced as risky and harmful, and are implicated in experiences of structural (and physical) violence and marginalization. Drawing on 50 qualitative interviews, this paper explores how spaces/places frequently used by structurally vulnerable people who use drugs (PWUD) in the DTES that are commonly associated with risk and harm (e.g., alleyways, parks) can be re-imagined and re-constructed as enabling safety and wellbeing. Study participants recounted both negative and positive experiences with particular spaces/places, suggesting the possibility of making these locations less risky and safer. Our findings demonstrate how spaces/places used by PWUD in this particular geographical context can be understood as assemblages, a variety of human and nonhuman forces – such as material objects, actors, processes, affect, temporal elements, policies and practices – drawn together in unique ways that produce certain effects (risk/harm or safety/wellbeing). Conceptualizing these spaces/places as assemblages provides a means to better understand how experiences of harm, or conversely wellbeing, unfold, and sheds light on how risky spaces/places can be re-assembled as spaces/places that enable safety and wellbeing. Highlights: Space/places in Vancouver's Downtown Eastside are implicated in experiences of inequity, marginalization, risk, and harm. Spaces of risk/harm in the Downtown Eastside have the potential to be re-constructed to enable safety and wellbeing. Spaces/places are understood as assemblages: human and nonhuman forces assembled in unique ways producing certain effects. Harnessing social resources of people who use drugs is key to implementing safe environment interventions/enabling places.